Circulating levels of IFN-γ, IL-1, IL-17 and IL-22 in pre-eclampsia: A systematic review and meta-analysis. (May 2020) - Deng, Ziwen; Zhang, Lu; Tang, Qian; Xu, Yinglei; Liu, Shiguo; Li, Hui
Abstract: Objective: Pre-eclampsia (PE) is a common multi-systemic disease, and the effect of cytokines on PE is not clear. The purpose of this meta-analysis was to evaluate the circulating levels of interferon gamma (IFN-γ), interleukin (IL)-1, IL-17 and IL-22 in patients with PE. Study design: Relevant studies were identified after a preliminary investigation of studies published up to May 2019 using PubMed and Embase. In this study, all 27 included articles underwent quality rating, with a total of 495 patients with PE and 557 controls. Among them, eight papers and 932 subjects contributed to the meta-analysis of IFN-γ, and six papers and 343 subjects contributed to the meta-analysis of IL-17. Based on the inclusion and exclusion criteria, the retrieved papers were screened and evaluated independently. Relevant data for IFN-γ and IL-17 were extracted for meta-analysis and subgroup analysis, and the stability of the results was evaluated by sensitivity analysis. At the same time, a systematic evaluation was carried out for IL-1 and IL-22 with a small number of included papers. Results: Several papers included in the systematic review showed that the circulating levels of IL-22 were higher in patients with severe PE than in controls, while IL-1 levels did not differ significantly between the two groups. The meta-analysis showed that patients with PE had higher circulating levels of IFN-γ than controls [standardized mean difference (SMD) 1.45, 95 % confidence interval (CI) 0.56–2.34]. There was no evidence of a difference in the circulating levels of IL-17 between patients with PE and controls (SMD 0.53, 95 %CI -0.43 to 1.48). Conclusion: This meta-analysis suggested that changes in circulating levels of IFN-γ might be associated with PE.